2022
DOI: 10.3390/metabo12100965
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Contributions Including Gender Differences and Metabolic Flexibility in the General Population and Athletes

Abstract: Metabolic flexibility includes the ability to perform fat and carbohydrate oxidation, as well as oxidative capacity, which is associated with mitochondrial function, energetic contributions, and physical health and performance. During a session of graded incremental exercise testing (GIET), we investigated metabolic flexibility, the contributions of three energy systems, and performances of individuals with different metabolic characteristics. Fifteen general population (GP; n = 15, male n = 7, female n = 8) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Our calculation revealed a percentage of 11.5 ± 2.9% which corresponds with the data from Diry and colleagues [ 17 ]. The used method is established to determine the proportions of the energy metabolism towards exercise [ 33 , 37 , 49 , 50 , 51 , 52 , 53 ]. However, our study showed a higher phosphagen contribution (10.9%) than the results from Diry et al [ 17 ] (1.5%) because of the different methodological calculations of the phosphagen system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our calculation revealed a percentage of 11.5 ± 2.9% which corresponds with the data from Diry and colleagues [ 17 ]. The used method is established to determine the proportions of the energy metabolism towards exercise [ 33 , 37 , 49 , 50 , 51 , 52 , 53 ]. However, our study showed a higher phosphagen contribution (10.9%) than the results from Diry et al [ 17 ] (1.5%) because of the different methodological calculations of the phosphagen system.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study showed a higher phosphagen contribution (10.9%) than the results from Diry et al [ 17 ] (1.5%) because of the different methodological calculations of the phosphagen system. The time constant of mono-exponential function using off O 2 kinetics, which indicates phosphocreatine (PCr) recovery (return to baseline PCr levels) after intense exercise, serves as a more precise method to consider the phosphagen contribution in our study [ 33 , 37 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that individualized low-intensity Pilates exercises may enhance aerobic endurance and energy recovery in adults. The tendency of a rightward shift of the exponential lactate curve can be indirectly explained by improved energetic recovery ability, including fat oxidation and ATP re-synthesis, along with aerobic endurance capacity in zones 1, 2, and 3 [ 12 , 13 , 25 , 31 ]. If low-intensity Pilates exercise is performed for more than 6-8 weeks, due to its low energy consumption, Pilates exercise would improve the mechanism of fat metabolism and mitochondrial function [ 12 , 13 , 25 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tendency of a rightward shift of the exponential lactate curve can be indirectly explained by improved energetic recovery ability, including fat oxidation and ATP re-synthesis, along with aerobic endurance capacity in zones 1, 2, and 3 [ 12 , 13 , 25 , 31 ]. If low-intensity Pilates exercise is performed for more than 6-8 weeks, due to its low energy consumption, Pilates exercise would improve the mechanism of fat metabolism and mitochondrial function [ 12 , 13 , 25 , 31 ]. Future studies with larger sample sizes are required to investigate how individualized low-intensity mat Pilates is related to other metabolism-related indices such as triglyceride, HDL-cholesterol, and fasting plasma glucose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation